PENGARUH PENGAWASAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR KEMENTERIAN PEKERJAAN UMUM DAN PERUMAHAN RAKYAT BALAI WILAYAH SUNGAI SUMATERA III PEKANBARU - Hendra, Teguh (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Human resources are the central figure in the organization to achieve the expected goals. In order for management activities to run well, an organization must have human resources who have high quality work and efforts to manage the organization as optimally as possible so that its performance can be maximized for many people. To create good work results, of course requires a good work supervision system as well. Supervision is one of the keys to the success of the organization in achieving its goals. The purpose of supervision is to be able to control employees so that they are able to work in accordance with the provisions and work standards that have been set. In general, the purpose of this study was to determine the effect of supervision on the performance of Civil Servants at the Office of the Ministry of Public Works and Public Housing at the Balai Sungai Sumatera III Pekanbaru. The number of samples in this study were 93 people. From the results of the validity test, the overall statement item between the monitoring variable and the performance variable is declared valid because the value of rcount > rtable (0.2039). The results of simple linear regression obtained the value of Y = 30.854 + 0.354X. From the results of the t test, the t-test value (2.838)> from the t-table value (1.98638) with a significant level of 0.006 <0.05 means that the monitoring variable has an effect on the performance variable. And the value of the coefficient of determination R2 is 0.081, meaning that the contribution or the magnitude of the influence of supervision on performance is 0.081 or 8.1% while the remaining 91.9% is influenced by other variables that are ignored or not examined in this study